Study on CO2 stripping from water through novel surface modified PVDF hollow fiber membrane contactor - Rahbari-Sisakht, M. (Elsevier, 2014)
Dry-wet phased inversion method was used to fabricate polyvinylidene fluoride (PVDF) hollow fiber membranes. Different concentration of surface modifying macromolecules (SMM) i.e., 2, 4 and 6 wt.% were used as additives in the spinning dope. In the phase inversion SMM migrates to the membrane surface and changes the surface morphology with chemical properties on the membrane surface. This modification results into larger pore size, higher gas permeance, effective surface porosity and water contact angle. The surface modified membrane was used in membrane contactor for CO2 stripping from water by using self-fabricated gas-liquid membrane contactor module. The result of CO2 stripping experiment shows that the performance of surface modified membrane is better than plain PVDF membrane. CO2 desorption flux increased with respect to SMM concentration, considerably. The membrane fabricated with 6 wt.% SMM as additive showed higher CO2 desorption flux and efficiency of 2.1 x 10(-3) (mol m(-2) s(-1)) and 80%, respectively at 200 ml/min of liquid flow rate. For this membrane CO2 stripping flux was investigated for different liquid phase temperature. It was found that desorption flux increased by increasing liquid temperature and the highest stripping flux was obtained in the temperature of 90 degrees C. The enhancement of the gas flow rate increased the CO2 desorption flux but this change was negligible.